2015
DOI: 10.1186/s13018-015-0188-6
|View full text |Cite
|
Sign up to set email alerts
|

Transfusions and blood loss in total hip and knee arthroplasty: a prospective observational study

Abstract: BackgroundThere is a high prevalence of blood product transfusions in orthopedic surgery. The reported prevalence of red blood cell transfusions in unselected patients undergoing hip or knee replacement varies between 21% and 70%. We determined current blood loss and transfusion prevalence in total hip and knee arthroplasty when tranexamic acid was used as a routine prophylaxis, and further investigated potential predictors for excessive blood loss and transfusion requirement.Methods/materialsIn total, 193 con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
88
2
10

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(109 citation statements)
references
References 33 publications
9
88
2
10
Order By: Relevance
“…The transfusion rate in this study was 15.6% in group 2 (straight-stem) and 8% in group 1 (short-stem), which are both lower than in most previously published studies [9,10,22,23]. There is a wide variation of reported transfusion rates after THA in the literature, ranging from 10 to 69% [9,10,22,23].…”
Section: Discussioncontrasting
confidence: 45%
See 1 more Smart Citation
“…The transfusion rate in this study was 15.6% in group 2 (straight-stem) and 8% in group 1 (short-stem), which are both lower than in most previously published studies [9,10,22,23]. There is a wide variation of reported transfusion rates after THA in the literature, ranging from 10 to 69% [9,10,22,23].…”
Section: Discussioncontrasting
confidence: 45%
“…There is a wide variation of reported transfusion rates after THA in the literature, ranging from 10 to 69% [9,10,22,23]. In a prospective observational study of 114 THA, the allogeneic transfusion rate was 18% [22].…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, several previous studies reported that RBC transfusion rates in hip or knee arthroplasties varied between 16 and 69% . In our study, the transfusion rates in total arthroplasties of joints except fingers and toes were relatively high at approximately 78%, but the transfusion rates and mean number of RBC units used in arthroplasties were relatively lower in general hospitals than those in other types of medical institutions.…”
Section: Discussionmentioning
confidence: 41%
“…Thus, understanding the current situation on the blood usage according to the types of surgeries and hospitals would be helpful in effective perioperative blood management. The use of tranexamic acid has been known to reduce the usage of RBC units . Also, preoperative Hb levels and operation time affect the amount of intraoperative RBC transfusion.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of BTs after total knee arthroplasty has been reported to be between 11% to 69%. [23,24] However, overall postoperative losses were significantly lower in patients with IV administration of TA (200 mL of blood less compared to group that did not receive TA). Also, the local means of TA administration was associated with lower overall losses, by 150 mL of blood.…”
Section: Discussionmentioning
confidence: 99%